Mendesain Pembangunan Berdasar Perspektif Sosial Budaya - Mudjahirin Thohir (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
The development is a deliberate design of cultural change to improve peple’s live. Change in people knowledge , behavior, or its facilities. However, the people who were the target of the development, not necessarily accept it. Why? It is related to how the strategy to bringing together the understanding between goverment, people, and the development executor.